Retroviral transfer of a human beta-globin/delta-globin hybrid gene linked to beta locus control region hypersensitive site 2 aimed at the gene therapy of sickle cell disease. - Takekoshi, K J (1995)
Human gamma-globin and delta-globin chains have been previously identified as strong inhibitors of the polymerization of hemoglobin S, in contrast to the beta-globin chain, which exerts only a moderate antisickling effect. However, gamma-globin and delta-globin are normally expressed at very low levels in adult erythroid cells, in contrast to beta-globin. We report the design of a beta-globin/delta-globin hybrid gene, beta/delta-sickle cell inhibitor 1 (beta/delta-SCI1) and its transduction by retrovirus-mediated gene transfer. The beta/delta-SCI1-encoding gene retains the overall structure of the human beta-globin gene, while incorporating specific amino acid residues from the delta chain previously found responsible for its enhanced antisickling properties. To achieve high expression levels of beta/delta-SCI1 in adult erythrocytes, the hybrid gene was placed under the transcriptional control of the human beta-globin promoter and the DNase I hypersensitive site 2 of the human beta locus control region. High-titer retroviruses were generated, and stable proviral transmission was achieved in infected cells. The mRNA expression levels of the beta/delta-SCI1 gene in infected, dimethyl sulfoxide-induced murine erythroleukemia cells approached 85% of the endogenous murine beta maj-globin mRNA, on a per gene basis, evidence that high gene expression levels were achieved in adult erythroid cells. Further evaluation of this strategy in transgenic animal models of sickle cell disease should assess its efficacy for the gene therapy of human patients.